The Impact of Neighborhood, Family, and Individual Risk Factors on Toddlers' Disruptive Behavior. Issue 5 (29th April 2014) - Heberle, Amy E.; Thomas, Yolanda M.; Wagmiller, Robert L.; Briggs‐Gowan, Margaret J.; Carter, Alice S.
<x xml:space="preserve">Abstract</x> Disadvantaged neighborhoods confer risk for behavior problems in school‐aged children but their impact in toddlerhood is unknown. Relations between toddlers' disruptive behavior and neighborhood disadvantage, family disadvantage, violence or conflict exposure, parent depressive symptoms, and parenting behavior were examined using multilevel, multigroup (girl–boy) models. Participants were 1, 204 families (mean child age = 24.7 months). Unique associations between disruptive behavior and all risk factors were observed, but the effect of neighborhood disadvantage was negligible when all of the more proximal factors were accounted for. The results suggest both that children in disadvantaged neighborhoods are at greater risk of behavior problems than children in nondisadvantaged neighborhoods and that optimal prevention/intervention work with these children will attend to proximal risk factors.